Micronutrients enhance macronutrient effects in a meta‐analysis of grassland arthropod abundance. Issue 12 (8th October 2020) - Prather, Rebecca M.; Castillioni, Karen; Kaspari, Michael; Souza, Lara; Prather, Chelse M.; Reihart, Ryan W.; Welti, Ellen A. R.
Abstract: Aim: Ongoing alterations to Earth's biogeochemical cycles (e.g., via fertilization, burning of fossil fuels, and pollution) are expected to impact plants, plant consumers and all subsequent trophic levels. While fertilization experiments often reveal arthropod nutrient limitation by nitrogen and phosphorus via effects on plant nutrient density and biomass, these macronutrients are only two of many nutrients important to arthropod fitness. Micronutrients are key to osmoregulation and enzyme function and can interact synergistically with macronutrients to shape the geography of arthropod abundance. We examine arthropod response to macro‐ and micronutrient fertilization as a function of nutrient type, application amount, duration, frequency, and plant responses to fertilization with the goal of addressing how ongoing alterations to biogeochemical cycles will shape future grassland food webs. Location: Global. Time period: 1987–2018. Major taxa studied: Invertebrates. Methods: We compiled a database of 62 studies to test the response of six arthropod trophic groups to multiple fertilizer types (compositions of varying macro‐ and micronutrients), quantities, application frequencies, and application durations. Additionally, we examined the role of plant nutrient content and biomass in mediating arthropod responses to fertilization. Results: Micronutrients applied alone had no effects on plant biomass or arthropod abundance. However, when added with macronutrients, micronutrients amplified the effect of N, P and K in promoting arthropod abundance, a synergy that did not affect plant biomass. Micronutrients thus catalysed the ability of macronutrients to promote arthropod abundance across all guilds studied. Main conclusions: In grasslands, the rules governing the abundance of autotrophs and their consumers appear to differ fundamentally in their response to Earth's changing biogeochemistry. By revealing the importance of micronutrients for arthropods using a global dataset, we highlight a stoichiometric mismatch between limits of plants and arthropods for metal cations whose biogeochemistry, along with N and P, are being actively rearranged in the Anthropocene.